Family Honor versus Child Protection: Legal Intervention in the Persistence of Child Marriage in Indonesian Communities - Dian Latifiani; Waspiah Waspiah (The Indonesian Journal of Legal Intervention in Social Problems, 2026)
Child marriage persists in Indonesia despite legal reforms intended to raise the minimum marriage age and strengthen children's protection. In many communities, decisions to marry children are influenced by family honor, pregnancy outside marriage, economic hardship, religious interpretations, and concerns about social stigma. This article examines why formal legal intervention has not fully displaced the social practices that sustain child marriage and how law can respond more effectively to these underlying conditions. Through a socio-legal approach, the study explores the interaction between marriage regulation, child protection, family decision-making, community norms, and judicial mechanisms for marriage dispensation. The analysis argues that legal prohibition alone is insufficient when families and communities perceive early marriage as a legitimate solution to social and economic problems. The article contributes by shifting the analysis of child marriage from regulatory compliance toward the effectiveness of law as a form of social intervention. It proposes a multidimensional approach involving stricter judicial scrutiny, community-based prevention, reproductive and legal education, socioeconomic support, and child-centered decision-making. Such intervention is necessary to ensure that legal protection addresses not only the occurrence of child marriage but also the social structures that reproduce it.